Artificial immune system assisted Minimum Variance Distortionless Response beamforming technique for adaptive antenna system - Salem.s B.; Kiong T.S.; Paw J.K.S.; Hock G.C. (IEEE Computer Society, 2023)
In wireless applications, the radiation pattern of adaptive antenna system is smartly formed and steered to cancel interfering signals (placing nulls) and produces a strong peak towards the desired signal according to the calculated weight vectors. This paper proposes an enhanced beamforming technique based on Minimum Variance Distortionless Response (MVDR). The Clonal selection algorithm (Clonalg) of Artificial Immune System (AIS) has been incorporated to assist MVDR to more precisely steer its beam towards desired user and forming deeper nulls at the interfering signals. The proposed algorithm has been simulated by using uniform linear antenna with multiple array elements, with 0.5? spacing between adjacent elements and operated in the frequency of 2.3GHz with 20 dB noise power level. Simulation results show that AIS assisted MVDR adaptive beamforming technique is able to produce much better received SINR in comparison of conventional MVDR. 2013 IEEE.